PILKADA LANGSUNG DAN STABILITAS PEMERINTAHAN DI JAWA TENGAH - Herawati, Nunik Retno (JURNAL ILMU SOSIAL, 2013)
Divided government in the District isvery interesting tostudy, in addition to a new phenomenon, the government was divided (split) basically could create instability ingovernance. Divided government was originally based on the assumption that the direct election results are not always consistent and in line with the results of legislative elections. In this sense the winner of the election  is not  automatic Direct  was  the winning  party  legislative  elections  because  of  voter  behavior  in local elections tend  to be more forward  Jump candidates  (figure) rather than political party clwice.The purpose of this study  were : First, analyze the results of  theelections Direct elections to the parliament members vote on a number of districts and munidpalities in Central Java; Second, look at the dynamics of political relations between the Regional Head  Elected  to parliament members ina number of districts and munidpalities in Central Java of the year 2005 to 2006.For thepurpose of thisstudy toanalyze bylooking at the voting results  Election  of Members  of  Parliament  and  electoral vote resulted directly in a number of districts and munidpalities in Central Java.  Once  it  was  done  in-depth  observations  on  each  government Kabupten/ City in Central Java.The conclusion of this research was the result of election districts Idties in Central Java during the period 2005 - 2006 showed that of the 26 districts/ dtieswhich have beencarrying out direct elections showed 50% of thearea marked witha divided government (divided Government).This showed that the Chief Elected Regional Winners Party was not carried by the legislative elections or a majority of seats inparliament .While 50% of the marked area of government that did not split  (unified government), which was carried by theelected Head of the Regional Legislative Election Winners Party (themajority ofseats inparliament).